Effect of Zinc Nitrogen and Phosphorus on the Yield and Uptake of Zine by Wheat in Loamy Sand Soil - Mathur, G M; Lal, F (Annals of Arid Zone, 2016)
In a field experiment, effect of zinc fertilization (0. 2.5, 5.0, 7.5, 10.0, and 12.5 kg Zn ha-’) was studied at two levels of nitrogen (60 and 120 kg N ha-1) and three levels of phosphorus (0.40 and 60 kg P2O5 ha-1) on the yield and uptake of zinc by wheat (Cv. Kalyan Sona) in an alkaline loamy sand soil having low contents of available nitrogen, phosphorus and zinc. A positive significant interaction of N, P and Zn on the grain and straw yield of wheat was observed The optimum dose of N, P2O5 ha-1 and Zn was found to be 120. 60 and 10 kg ha-1, respectively. Zinc uptake by wheat crop increased with an increase in the levels of applied N, P and Zn.